2020
DOI: 10.3390/su122410299
|View full text |Cite
|
Sign up to set email alerts
|

Regional Security Assessment of Integrated Energy Systems with Renewables in China: A Grid-Connected Perspective

Abstract: Stable and reliable integrated energy systems are one of the major issues related to sustainable regional and national energy development. Because most existing studies are conducted on whole countries, few address the effects of regional interaction and renewable energy. Therefore, a natural disaster risk assessment model (NDRAM) combined with spatial models is used as a general systematic tool to assess and resolve regional energy security, based on a framework of resources, generation, transmission, marketi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Photovoltaic installations are very popular because they are available to most people, and their installation does not require as much capital as in the case of installations using other renewable energy sources which is confirmed by many authors in their works [1][2][3][4][5]. In addition, along with the development of technology, they are becoming cheaper and more effective way to obtain electricity [6][7][8]. Currently, little attention is paid to the problem of recycling waste generated as a result of the development of the photovoltaic industry, but in the coming years it may turn out to be a big mistake.…”
Section: Introductionmentioning
confidence: 94%
“…Photovoltaic installations are very popular because they are available to most people, and their installation does not require as much capital as in the case of installations using other renewable energy sources which is confirmed by many authors in their works [1][2][3][4][5]. In addition, along with the development of technology, they are becoming cheaper and more effective way to obtain electricity [6][7][8]. Currently, little attention is paid to the problem of recycling waste generated as a result of the development of the photovoltaic industry, but in the coming years it may turn out to be a big mistake.…”
Section: Introductionmentioning
confidence: 94%
“…The main themes of energy supply security have changed slightly as the interests of society, technology trends, and geopolitical and economic situations change. The definition of energy supply security has been represented by a number of factors such as availability [12,13], infrastructure [13], energy price [12,14,15], environment [15][16][17], efficiency [15,18,19], social effects [17], and governance [19]. These definitions have even varied depending on the target application domains and their detailed subjects.…”
Section: Literature Review 21 Global Level Analysis Of Energy Supplmentioning
confidence: 99%
“…From a more specific and comparative perspective, many studies have been conducted at regional and national levels [13,[24][25][26][27][28][29][30]. Le et al [24] reported the different levels of energy insecurity in Asia, focusing on 12 variables such as CO 2 emissions, CO 2 intensity, energy imports, energy intensity, energy use, fossil fuel energy consumption, and renewable energy consumption.…”
Section: Regional and National Level Analysis Of Energy Supply Securitymentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, despite the high dependence on fossil fuels, Australia has achieved a model of transition of the energy system, promoting it towards more renewable resources. In the same way, China has set goals to be a green economy and resilient, as indicated in [2,3]. A green transition in the Central America region requires introducing novel policies and technology to consider all the region's power sector dimensions.…”
Section: Introductionmentioning
confidence: 99%